2015
DOI: 10.1002/lary.25822
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of high‐risk and low‐risk oral HPV infection in the United States

Abstract: 4. Laryngoscope, 126:1365-1372, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 21 publications
(50 reference statements)
0
16
0
Order By: Relevance
“…Similarly, the 2009–2010 NHANES documented that the prevalence of oral HPV infection in the US was 6.9%, and no significant differences were found by gender or race/ethnicity [5] . Nonetheless, more recent US data showed a prevalence of infection of 8.1%, and lower odds of infection with low-risk HPV types among non-Hispanic Whites compared to Hispanics [6] . Lower odds of both low-risk and high-risk HPV infections were also seen for women in the NHANES studies.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Similarly, the 2009–2010 NHANES documented that the prevalence of oral HPV infection in the US was 6.9%, and no significant differences were found by gender or race/ethnicity [5] . Nonetheless, more recent US data showed a prevalence of infection of 8.1%, and lower odds of infection with low-risk HPV types among non-Hispanic Whites compared to Hispanics [6] . Lower odds of both low-risk and high-risk HPV infections were also seen for women in the NHANES studies.…”
Section: Discussionmentioning
confidence: 94%
“…While the prevalence of HPV in oropharyngeal cancers has increased, with estimates of 72% in North America, Europe and other populations [4] , prevalence of oral HPV infection in cancer-free individuals, risk factors, natural history, and transmission mechanisms remain largely unexplored. In the US, prevalence estimates of oral HPV infection were 6.9% in 2009–2010 5 and 8.1% during 2009–2012 [6] . Oral sex, male gender, older age, open-mouthed kissing, increasing number of sexual partners, HIV infection, tobacco, and marijuana and heavy alcohol use have been associated with oral HPV infection [5] , [7] , [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Yet meanwhile, national trends show significant increases in HPV-related HNSCCs [13,14], particularly among non-Hispanic white and black males [15]. These trends correlate with increases in sexual behaviors associated with oral HPV infection [16,17], with the strongest associations among men [18]. …”
Section: Introductionmentioning
confidence: 99%
“…The behavioral risk factor for HPV-OPC is oral sex. 7 Not surprisingly, a Dutch study found that women with a history of cervical intraepithelial neoplasia 3 had an increased, long-term risk for HPV-OPC compared with matched controls. 8 Patients with HPV-OPC are also less likely to be users of tobacco products and/or alcohol and have a higher functional status.…”
mentioning
confidence: 99%